(untitled) (Cardiovascular Journal, 2011)
With the advent of live/real time three-dimensional (3D) echocardiography, 3D imaging as a research tool has evolved to a clinical mainstay. In this review, we discuss procedures for and application of 3D echocardiography to specific clinical questions. Although contemporary application remains primarily for assessment of left ventricular function, we review many more uses for this truly revolutionary technique. DOI: http://dx.doi.org/10.3329/cardio.v1i1.8197 Cardiovasc. j. 2008; 1(1) : 3-13